Conceptualization of the Indo-Pacific in Russia’s “Turn to the East” - Rozman, Gilbert (AEI Insights, 2023)
Rejecting the constructs “Indo-Pacific” and the “Quad,” Russians use their own label, “Greater Eurasia” to characterize the architecture gaining ascendency in Asia. They insist that this is consistent with China’s “Belt and Road Initiative.” Yet, its clear purpose is to reject a China-centered region, showcasing the role of India and ASEAN in multipolar regionalism. Recent tensions between China and India and India’s embrace of the “Indo-Pacific” label complicate the Russian narrative. The Ukraine war has driven Russia closer to China, but hesitancy in India and some Southeast Asian states to criticize it leaves room for Russian rhetoric about “Greater Eurasia” to persist.